Applying Time-Bound Hierarchical Key Assignment in Wireless Sensor Networks - ZHU, Wentao (Institutional Knowledge at Singapore Management University, 2011)
Access privileges in distributed systems can be effectively organized as a partial-order hierarchy that consists of distinct security classes, and are often designated with certain temporal restrictions. The time-bound hierarchical key assignment problem is to assign distinct cryptographic keys to distinct security classes according to their privileges so that users from a higher class can use their class key to derive the keys of lower classes, and these keys are time-variant with respect to sequentially allocated temporal units called time slots. In this paper, we explore applications of time-bound hierarchical key assignment in a wireless sensor network environment where there are a number of resource-constrained low-cost sensor nodes. We show time-bound hierarchical key assignment is a promising technique for addressing multiple aspects of sensor network security, such as data privacy protection and impact containment under node compromise. We also present the technical challenges and indicate future research directions.